PERANCANGAN SISTEM PAKAR IDENTIFIKASI PENYAKIT DAN HAMA TANAMAN ANGGREK DENGAN METODE CERTAINTY FACTOR - Wahyuni, Rosmala Eka (JUSTIN (Jurnal Sistem dan Teknologi Informasi), 2015)
Diseases and pests is one of the obstacles in plant cultivating, especially orchids. Disease infection and pests can damage the cultivation of orchids and effecting the beauty of orchids. Problems that occur around the orchid plant diseases and pests that are often experienced by orchid farmers itself is they cant tell between orchid diseases and pests due to thee lack of knowledge about the disease and pest itself. Diseases mistaken pests and pest mistaken diseases. Orchid disease is the cause of orchids becoming ill, usually caused by the infection of microorganisms such as fungi, bacteria and viruses. Orchid pests are orchids vermin. To differ between orchid diseases and pests, identification is needed to be done so the cultivators of orchids can easily know if it is the disease or pest that is experienced by orchids. Another problem is the lack of an expert or expertees in diseases and pests of ornamental plants, especially orchids, making cultivators having difficulty in overcoming diseases and pests of orchids. An expert system is one solution in identifying orchid diseases and pests based on symptoms experienced by orchids. In this study an expert system is made by applying certainty factor, the application is developed to determine the diseases or pests on orchids with only paying attention to the symptoms experienced by orchids. By applying the method certainty factor possible values are obtained for the infection of the disease or pest attack suffered orchids. The system produce can proses data management and identify disease or pest with a accurate level of 80 %. The symptoms data inputed will be processed until there are identification results that are accordance to the certainty factor.